Pengaruh Terapi Kelompok Terapeutik Kombinasi Project Based Learning terhadap Stimulasi Perkembangan Psikososial Remaja menggunakan Pendekatan Peplau - Keksi Girindra Swasti; Herni Susanti; Ice Yulia Wardani (Journal of Bionursing, 2023)
Background: Youth are the next generation of the nation that has the right to grow healthy and prosperous in order to participate in development. Therapeutic group therapy (TKT) is an effective intervention to improve the developmental ability and self-identity formation of adolescents.The combination of TKT and Project Based Learning (PjBL) will provide challenges to be conquered so as to build youth resilience. Success in mastering developmental tasks and challenges will bring youth happiness. Methods: The design used was a quasi-experimental one-group pre-post test design and purposive sampling technique The achievement is measured in the form of psychological well-being. PjBL combination TKT activities were conducted in Blangkunan Village Pabelan On February 22 - May 7, 2021. The activity was attended by 17 youth divided into three groups, groups 1 and 2 each 6 people, and group 3 consisting of 5 people. TKT activities are conducted as many as 6 sessions with a time per meeting of 60-90 minutes.Results: The majority of adolescents are female (70.6%). There is an increase in all aspects of adolescent development, namely 100% in cognitive, language, emotional, personality, moral, spiritual, social, and creative skills. Aspects of talent development increased 58.82%. Increased resilience of adolescents from 69.7% to 75.45%. while psychological well-being increased from 68.67% to 70.63%. Conclusion: Combination therapeutic group therapy PjBL improves the ability aspects of biological development, psychosocial, cognitive, language, emotion, personality, moral, spiritual, social, talent and creativity; resilience, and psychological well-being teenagers.